The impact of consumption values towards the intention to visit green hotel in Malaysia: the moderating effect of environmental concern / Nur Shakinah Joibi - Joibi, Nur Shakinah (2022)
Due to Malaysia's beautiful natural assets, Malaysia's tourism industry has experienced steady growth over the decades. Tourism is increasingly dependent on a clean climate, so it is not possible to disregard hotel operational waste problems. It can be anticipated that customer actions can create loads of waste while staying in the hotel. As a result, the transition to a green customer has become a step to resolve this problem. The purpose of this paper is to investigate the impact of consumption values towards intentions to visit green hotel in Malaysia. A multi-dimensional measure of consumption values was used to determine which values of consumption are valued by local and international tourists. The Theory of Consumption Values (TCV) employed and modified in this study. The consumption values in this study have impact on intention to visit green hotel in Malaysia while environmental concern as the moderator. In many adventures in tourisms’ items, epistemic value is a key factor because visitors want to experience discovery and pursue distinct behaviours (Zuckerman, 1994). An existing marketing paradigm was introduced in this study and the relationships between epistemic value, environmental concern, and behavioural intentions in an adventure tourism context were explored empirically. The outcome illustrates that environmental concern has a moderating impact on the epistemic value of intention to visit a green hotel. Three hundred and twenty-two respondents over the age of 18 years are international and local visitors. The questionnaire is used, and the data analysis been analysed by using the Statistical Package for Social Sciences (SPSS) and the Lesser Plane (PLS).